Pengaruh Profil Leukosit dan Eritrosit Sapi Bali Jantan yang Digemukkan dengan Complete Feed yang Mengandung Level Protein Kasar Berbeda - Yulius Luan Halek; Paulus Klau Tahuk; Gerson Frans Bira (JAS, 2021)
The purpose of this study was to determine the leukocyte profile and erythrocytes of Balinese bulls fattened with complete feed containing different levels of crude protein (CP). Cattle used were 2 - 2.5 years old male Balinese cows with initial weights of 200 kg. The ration used is a complete feed which is composed of feed material in the form of natural grass, gamal flour, rice bran, milled corn, pollard bran. The variables measured in this study are the content of leukocytes and erythrocytes. The method used is an experimental method using a completely randomized design (CRD) with the following treatment: T1: 27% natural grass + Gliricidia sepium 10% + Corn 34% + Pollard 15% + Rice Bran 14% T2: natural grass 27% + 20% Gliricidia sepium+ 18% corn + 15% pollard + 10% rice bran T3: 27% natural grass + 13% Gliricidia sepium + 20% corn + 15% pollard + 7% rice bran. The results of this study indicate that the use of complete feed with different CP levels does not affect the content of erythrocytes and leukocytes of male Bali cattle. Where the contents of the erosion (106 / µI) each treatment was T1: 11.08; T2: 10,30; T3: 10,99; Leukocyte content (103 / µI) of male Bali cattle each treatment was T1: 10,51; Q2: 11,59; T3: 10,48; Based on the results of research that has been done, it can be concluded that the provision of complete feed with CP level (11%, 13%, 15%). With energy (72% TDN) gives the same effect to all treatments and produces Erythrocytes and Leukocytes content in the normal range.